The physical approximation of APP and BACE‐1: A key event in alzheimer's disease pathogenesis. Issue 3 (13th November 2017) - Sun, Jichao; Roy, Subhojit
ABSTRACT: Alzheimer's disease (AD) is characterized by the accumulation of insoluble deposits of Amyloid β (Aβ) in brains. Aβ is derived by sequential cleavage of the amyloid precursor protein (APP) by β‐site secretase enzyme (BACE‐1) and γ‐secretase. Proteolytic processing of APP by BACE‐1 is the rate‐limiting step in Aβ production, and this pathway is a prime target for AD drug development. Both APP and BACE‐1 are membrane‐spanning proteins, transported via secretory and endocytic pathways; and the physical interaction of APP and BACE‐1 during trafficking is a key cell biological event initiating the amyloidogenic pathway. Here, we highlight recent research on intracellular trafficking/sorting of APP and BACE‐1, and discuss how dysregulation of these pathways might lead to enhanced convergence of APP and BACE‐1, and subsequent β‐cleavage of APP. © 2018 Wiley Periodicals, Inc. Develop Neurobiol 78: 340–347, 2018